Optimization of Pre-Splitting Blasting Hole Network Parameters and Engineering Applications in Open Pit Mine - Ziyi Wang; Guiyi Wu; Lang Zhou (Applied Sciences, 2022)
In order to optimize the parameters of a pre-splitting blasting hole network, taking an open-pit mine in Inner Mongolia as the engineering background, the numerical models of different pore sizes and hole spacing were established by LS-DYNA software. The stress wave propagation law, peak stress change and rock fracture state under various working conditions were analyzed. The optimization formula of a hole network relationship was proposed and verified on site. The results show that the shock wave generated by the explosion propagates rapidly upward from the explosion source and forms a plastic flow zone around the two boreholes. The energy consumption is the largest at this stage. With the propagation of the stress wave, energy dissipates, and its waveform gradually attenuates to a compression wave and seismic wave. In each working condition, a 110 mm aperture first cracked in the stress wave superposition area compared with other working conditions, while a 120 mm aperture delayed evolution to the seismic wave compared with different borehole aperture, and the energy attenuation rate is the slowest. Meanwhile, the fastest energy attenuation rate is with the 130 mm borehole aperture. With the attenuation of the propagation energy of the stress wave, among the four measuring points set at the center of the connection between the two boreholes, the Y-direction stress of the observation points B, C and D is stable between 2.3 and 3.5 MPa, and the Y-direction stress of the observation point A is strenuous between −1.3 and 1.2 MPa. The B, C and D observation points of 90–130 mm aperture conditions showed rock cracking at 7–9 times, 7–9 times, 7–10 times, 7–11 times, and 7–11 times hole spacing, respectively. The cracks of the two boreholes were interconnected. The optimal hole network relationship is obtained by fitting: y = 1.12 + 0.076x, where y is the optimal hole diameter and hole spacing multiple, and x is the hole diameter, which is verified by engineering. After blasting, the slope is smooth and smooth, and the half-hole rate is guaranteed to be above 90%.